Action to reduce poverty: proposals for needed initiatives developed by a Commonwealth Consultation on Rural Poverty Alleviation (Commonwealth Secretariat LondonUK, 1993)
Examines issues such as - defining the problem and characterising the poor; poverty-specific policy approaches; poverty programme design, development and delivery; resources and the sustainability of poverty alleviation programmes; integrating poverty alleviation programmes into overall development strategies; and the roles of those involved in poverty alleviation programmes.
DC